Investigation of the physical causes of improved machinability of steel alloyed with calcium - Amin, A. K. M. Nurul; A. l., Kurchenko; N. P., Talantov (1984)
Investigations have been carried out to determine the possibility of improving machinability of steel by alloying with calcium or other ingredients and also to explain the physi¬cal causes of improved machinability. Results of the experiments show that machina¬bility of steel can be raised several times without adversely affecting its physiomechanical properties. Causes of the improvement of machinability higher degree of hardening of the sulphides due to micro alloying with calcium. Hardened sulphides are ca¬pable of effectively resisting the movement of dislocations in the chip-tool plastic contact zones and as a result the percentage of the total work of plastic deformation spent in changing the internal energy of metal is much higher in the case of alloyed steel than that of the normal steel. And consequently the percentage of total work spent in raising the cutting temperature is much lower in the case of the alloyed steel. Relatively lower value of cutting temperature ultimately facilitates higher tool life, i.e. higher machinability of calcium alloyed steel.